(3GdJjSjQ aj bhGYO Yde GdJaSjQs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GfRd GdbQBf QMeI ddCfGe GdPi fTQ GdaQbGf hHjf GdCMcGe s
(3BNQgG (B:s
(3aCYjPg ai faS ef MGSOkG SeY GdbQjV abGd ajg hGLd s
(3UaMI GdYfhGf ePgHIs
(3jYi GdcJGH fbd ai Yde GdJaSjQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B520s
Keywords: (3GdJaSjQ hYdhe GdbQBfs